Teaching and didactics: perceptions of those who train the teacher - Silva, Edileuza Fernandes (2022)
The purpose of this article is to discuss the perceptions of teaching and specific didactics of coordinators and teachers of undergraduate courses at the University of Brasilia. The courses involved were: Portuguese Language, Modern Foreign Language - English, Physical Education, Mathematics, History, Geography, Physical and Biological Sciences. The qualitative approach was used to analyze data from questionnaires and semi-structured interviews. We conclude that the perceptions of the teachers about specific didactics are based on the political-pedagogical, technical, professional, training with research, dialogical, theoretical-practical and problematizing dimensions; and that in face of the complexity of the teaching work, it is fundamental that the undergraduate courses make institutional efforts to consolidate specific didactics in the teacher training curricula.